Developing an Eye-Tracking Protocol to Determine Children's Visual Perception of Secondary Cleft Lip Deformity. (March 2020) - Karp, Emily; Scott, Andrew; Martin, Katherine; Zavala, Hanan; Chinnadurai, Siva; Roby, Brianne
Objective: To develop a protocol that will be used to measure children's perception of secondary cleft lip deformity (SCLD) using objective eye-tracking technology. Design: Cross-sectional study. Data collection May and June of 2018. Setting: Single tertiary care pediatric hospital with a well-established cleft team. Participants: Participants were recruited from a general pediatric otolaryngology clinic. Sixty participants from 4 age groups (5-6, 10, 13, and 16 years) were enrolled on a voluntary basis. Intervention: Pediatric participants viewed images of children's faces while wearing eye-tracking glasses. Ten images with unilateral SCLD and 2 control images with no facial scarring were viewed as gaze was assessed. Main Outcome and Measure: Successful gaze fixation was recorded across all age groups. Results: This article illustrates the types of data generated from glasses-based eye tracking in children. All children, regardless of age, spent more time with their gaze on a SCLD images (mean = 4.23 seconds; standard deviation [SD] = 1.41 seconds) compared to control images (mean = 3.97 seconds; SD = 1.42). Younger age groups spent less time looking at specific areas of interest in SCLD images. Conclusion: In this pilot study, we were able to successfully use eye-tracking technology in children to demonstrate gaze preference and a trend toward visual perception of SCLD changing with age. This protocol will allow for a future study, with larger and more diverse populations. Better understanding of how SCLD is perceived among children and adolescents has the potential to guide future interventions for SCLD and other facial deformities in pediatric patients.